한⋅중⋅일 국가별 극지활동 비교 연구 - 김단비; 김봉철 (Journal of Global and Area Studies , 8(3), 2024)
이 글은 비극지권 국가이지만 극지와 관련 연구 및 활동을 활발히 수행해오고 있으며, 남 극조약 체계를 준수하고 2013년 북극이사회 옵저버 국가로 승인되는 등 극지 지역에 대한 공통점을 가지고 있는 동북아 주요 국가 중 한국, 중국, 일본 3국의 극지 활동에 공통점과 차이점이 무엇인지에 대한 문제의식에서 시작하였다. 이러한 인식하에 실제 세 나라의 극지 관련 활동을 시기별, 특징별로 분석하여 공통점과 차이점을 알아보고, 구체적으로 북극과 남 극에 대한 각국의 기본 활동 사항과 목표 등을 제시하고자 하였다. 마지막으로 향후 극지 활 동이 어떠한 방향으로 이루어져야 하는지에 대한 제언을 제시하고자 하였다. 결론적으로 세 국가는 국제사회에 대한 이전보다 더 많은 기여와 역할이 요구되고 있고 극지역 정치에 있어서도 중립적 이해당사자로서 나아가 국제사회에서 오피니언 리더로 부상 하고 있기 때문에 장기적으로 새롭게 떠오르는 극지역 이슈에 유연하게 대응할 수 있도록 꾸 준한 연구활동을 이어나가야 하며, 한ㆍ중ㆍ일 세 국가가 지속적으로 협력할 수 있는 부분을 찾아 발전시키는 노력이 이루어져야 할 것이다. 또한, 향후 세 국가의 극지와 관련한 연구 및 탐험 활동의 개선이 주요한 국가 과제로 인식되어야 하고, 단편적인 문제를 해결하기보다 는 장기적인 관점과 타 분야와의 연관성을 발견하여 다차원적인 대응 방향을 끊임없이 마련 하여 다른 비극지권 국가들의 극지정책 참여와 정책 마련에 기여할 수 있는 선도적 국가로서 발전해 나가야 할 것이다. This paper begins with the awareness of the commonalities and differences in polar activities among the three major Northeast Asian countries Korea, China, and Japan which, although not polar nations, have been actively conducting research and other related activities regarding polar regions. They adhere to the Antarctic Treaty System and were approved as observer states in the Arctic Council in 2013. With this understanding, the paper aims to analyze the polar-related activities of these three countries by period and characteristics to identify commonalities and differences. Specifically, it seeks to present the basic activities and goals of each country concerning the Arctic and Antarctic and to offer suggestions on the future direction of polar activities. According to this, the three countries are now required to contribute more and play greater roles in the international community. As neutral stakeholders in polar region politics and emerging opinion leaders globally, they need to continue steady research activities to flexibly respond to new polar issues in the long term. Efforts should be made to find and develop areas where Korea, China, and Japan can continuously cooperate. Furthermore, the improvement of research and exploration activities related to polar regions should be recognized as a major national task for all three countries. Instead of addressing issues in a fragmented manner, they should take a long-term perspective, identify links with other fields, and continuously develop multidimensional response strategies. This approach will help them evolve into leading nations that contribute to the participation and policy formulation of other non-polar countries in polar policies. KCI Citation Count: 0